2018
DOI: 10.1007/s10695-018-0494-0
|View full text |Cite
|
Sign up to set email alerts
|

Response of gastrointestinal melatonin, antioxidants, and digestive enzymes to altered feeding conditions in carp (Catla catla)

Abstract: The purpose of present study was to ascertain whether the response of gastrointestinal (gut) melatonin to altered feeding conditions was related to the levels of different antioxidants and digestive enzymes in the same gut tissues of a sub-tropical carp (Catla catla). Accordingly, the fish were subjected to food deprivation for 4 or 8 days and separately to re-feeding for 4 or 8 or 12 days after deprivation of food for 8 days, and their gut tissue homogenates were used to measure the levels of melatonin, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Colossoma macropomum , subjected to 7-weeks of feed starvation in the re-feeding stage showed a drastic increase in amylase activity 26 . The increased digestive enzyme activity in re-alimentation phase was due to the increased availability of feed, after a food restriction period 30 . In rainbow trout, significantly reduced lipase activity reported during starvation phase, however, the reduced activity was successfully restored in re-feeding phase 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Colossoma macropomum , subjected to 7-weeks of feed starvation in the re-feeding stage showed a drastic increase in amylase activity 26 . The increased digestive enzyme activity in re-alimentation phase was due to the increased availability of feed, after a food restriction period 30 . In rainbow trout, significantly reduced lipase activity reported during starvation phase, however, the reduced activity was successfully restored in re-feeding phase 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Its production in GI tract is several hundred-folds higher than produced in the pineal gland (16,23,24,26). Its synthetic enzymes have been found in the GI tissues (19,24,23,25). The melatonin in GI tract is to regulate the physiological activities (14-16, 18-19, 21, 26) and locally protect GI tissue from the free radical damage (14-15, 18-19, 22).The mechanism study indicated that the gene expression of the melatonin synthetic enzyme, AANAT and its membrane receptor, MT1 was significantly down regulated by adrenaline.…”
Section: Discussionmentioning
confidence: 99%
“…The melatonin in GI tract is to regulate the physiological activities (14-16, 18-19, 21, 26) and locally protect GI tissue from the free radical damage (14-15, 18-19, 22).The mechanism study indicated that the gene expression of the melatonin synthetic enzyme, AANAT and its membrane receptor, MT1 was significantly down regulated by adrenaline. The decreased melatonin production is always associated with oxidative damage in tissues and organs (14,(19)(20). The pro-oxidation of adrenaline can cause DNA damage and impact the integrity of DNA (4, 52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include use of some neuro-endocrine hormones, neurotransmitters, and growth factors which show promising effects in inhibiting the detrimental changes induced by the stressors (18)(19)(20). Among these, melatonin is considered as the most promising agent due to its lipophilic nature, paracrine actions, broad spectrum antioxidant and direct free radical scavenging properties (21)(22)(23)(24)(25)(26). High levels of melatonin presence in bile (27) and GI tract (25,28,29) of mammals including humans (30) provide a unique advantage to overcome many pathological conditions in these tissues.…”
Section: Introductionmentioning
confidence: 99%